2014
DOI: 10.1371/journal.pone.0096486
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Wide Association Study of Plasmodium falciparum Susceptibility to 22 Antimalarial Drugs in Kenya

Abstract: BackgroundDrug resistance remains a chief concern for malaria control. In order to determine the genetic markers of drug resistant parasites, we tested the genome-wide associations (GWA) of sequence-based genotypes from 35 Kenyan P. falciparum parasites with the activities of 22 antimalarial drugs.Methods and Principal FindingsParasites isolated from children with acute febrile malaria were adapted to culture, and sensitivity was determined by in vitro growth in the presence of anti-malarial drugs. Parasites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…33 Bray et al showed that PQ potentiates CQ versus some CQR strains, 34 and recent genomewide association studies demonstrate increased sensitivity to PQ in some CQR isolates. 33 However, it is not clear whether this reciprocal relationship is due to PQ blocking CQ transport by PfCRT or perhaps to PQ transport by PfCRT in some of these strains. 34,36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Bray et al showed that PQ potentiates CQ versus some CQR strains, 34 and recent genomewide association studies demonstrate increased sensitivity to PQ in some CQR isolates. 33 However, it is not clear whether this reciprocal relationship is due to PQ blocking CQ transport by PfCRT or perhaps to PQ transport by PfCRT in some of these strains. 34,36 …”
Section: Resultsmentioning
confidence: 99%
“…These data suggest inhibition of Dd2 PfCRT CQ transport by PQ is due to isoform-specific competition between the two drugs for transport, which is consistent with the recently observed reciprocal relationship between CQR status and PQ susceptibility for African P. falciparum isolates. 33 …”
Section: Resultsmentioning
confidence: 99%
“…The parasite undergoes continuous growth and development, throughout the different stages of its life cycle. With the chance of mutations, these may be associated with the parasite becoming resistant to drugs [48; 49; 50; 51]. The transfer and propagation of offspring within and between its hosts is requisite for its survival, and modeling efforts are of paramount importance to project and understand individual and population-based parasite loads, transmission and disease characteristics, and treatment regimens, as well as to devise new means for intervention [52; 53].…”
Section: Malaria As the Paradigm Infectious Diseasementioning
confidence: 99%
“…2a and b). This high analytical sensitivity and specificity is important because, in high transmission areas, most parasitemias comprise many unique parasite genomes6171840 and traditional genotyping approaches may either fail to generate analyzable data owing to complex templates or fail to capture minority variant subpopulations; these minority variant populations can harbor clinically-important genotypes41. The correlations between observed and expected allele frequencies in control DNA samples for pf-ama1 were lower than those reported in studies employing whole genome sequencing of polygenomic templates42.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the utility of these approaches is undermined by the polyclonality common to high transmission regions such as Sub-Saharan Africa due to diversity at the same nucleotides in multiple parasites within individual patients1416. More recent approaches use NGS platforms to reconstruct whole genomes, but this approach is complicated by the parasite’s genomic architecture, polyclonality of parasitemias, and the need for sophisticated genome-scale assembly and analytic tools61718. NGS platforms have also been employed in ecological studies to sequence amplicons generated from pools of parasites1920, but heretofore technical constraints have limited the ability to assign sequence reads to individual input parasites.…”
mentioning
confidence: 99%